Spectra of Some Charmed Hadrons in a Non Relativistic Model - Harsha, T.; Anil Bokade, Chaitanya; Kaushal, Raghavendra; Bhaghyesh (East European Journal of Physics, 2025)
In a non-relativistic framework the mass spectra of cĉ, cc, ccc and ccu systems are investigated. The potential consists of the Cornell potential along with a logarithmic correction term as suggested from lattice QCD. We analyze the S, P, and D wave charmonium states and, S and P wave cc diquark states and have compared them with existing results from experiments and other potential models. Using the quark-diquark model, we have evaluated the S-wave spectra of doubly charmed baryon Ξ++cc and the triply charmed baryon Ωccc. These masses are compared with other theoretical studies.